Acidosis activates complement system in vitro. Issue 6 (1998) - Emeis, Michael; Sonntag, Josef; Willam, Carsten; Strauss, Evelyn; Walka, Matthias M.; Obladen, Michael
Abstract : We investigated the in vitro effect of different form s of acidosis (pH 7.0) on the formation of anaphylatoxins C3a and C5a. Metabolic acidosis due to addition of hydrochloric acid (10 μ mol/ml blood) or lactic acid (5.5 μ mol/ml) to heparin blood( N = 12 ) caused significant activation of C3a and C5a compared to control (bothp = 0.002 ). Respiratory acidosis activated C3a( p = 0.007 ) and C5a( p = 0.003 ) compared to normocapnic controls. Making blood samples with lactic acidosis hypocapnic resulted in a median pH of 7.37. In this respiratory compensated metabolic acidosis, C3a and C5a were not increased. These experiments show that acidosis itself and not lactate trigger for activation of complement components C3 and C5.